2015
DOI: 10.18632/oncotarget.3591
|View full text |Cite
|
Sign up to set email alerts
|

Resistin and interleukin-6 exhibit racially-disparate expression in breast cancer patients, display molecular association and promote growth and aggressiveness of tumor cells through STAT3 activation

Abstract: African-American (AA) women with breast cancer (BC) are diagnosed with more aggressive disease, have higher risk of recurrence and poorer prognosis as compared to Caucasian American (CA) women. Therefore, it is imperative to define the factors associated with such disparities to reduce the unequal burden of cancer. Emerging data suggest that inherent differences exist in the tumor microenvironment of AA and CA BC patients, however, its molecular bases and functional impact have remained poorly understood. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 54 publications
3
107
0
Order By: Relevance
“…About 80–90% of prostate cancer specimen indicate the signs of immune infiltration (55). Besides immune cells, cancer-associated fibroblasts (CAFs) present in TME also participate vigorously in growth and aggressiveness of the tumor by secreting several chemokines, cytokines, growth factors and other inflammatory mediators (56,57). CAFs communicate with cancer cells and immune cells through direct cell contact or by paracrine/exocrine signaling.…”
Section: Role Of Aberrantly-activated Signaling Pathways In Prostamentioning
confidence: 99%
“…About 80–90% of prostate cancer specimen indicate the signs of immune infiltration (55). Besides immune cells, cancer-associated fibroblasts (CAFs) present in TME also participate vigorously in growth and aggressiveness of the tumor by secreting several chemokines, cytokines, growth factors and other inflammatory mediators (56,57). CAFs communicate with cancer cells and immune cells through direct cell contact or by paracrine/exocrine signaling.…”
Section: Role Of Aberrantly-activated Signaling Pathways In Prostamentioning
confidence: 99%
“…The seeded cells were washed twice with PBS (1X) to remove spent media and serum. The lipofectamine 2000-siNA complexes were added to the cultures and incubated for 5 h and then media containing 20 % serum was added and transfected cells were further incubated for 20 h [23,24].…”
Section: Short-interfering Molecule Preparationmentioning
confidence: 99%
“…Several mechanisms have been proposed for chemoresistance of BC, which may involve both intrinsic and extrinsic factors [10, 11]. Tumor microenvironment (TME) is comprised of a heterogeneous mixture of many different cells that produce and secrete a number of growth factors and cytokines [12, 13]. Interestingly, a recent study suggested the existence of disparate TME in AA vs. CA breast tumors [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor microenvironment (TME) is comprised of a heterogeneous mixture of many different cells that produce and secrete a number of growth factors and cytokines [12, 13]. Interestingly, a recent study suggested the existence of disparate TME in AA vs. CA breast tumors [1315]. Emerging data have provided convincing evidence for an important role of TME in cancer chemoresistance, which involves both direct and indirect mechanisms [16, 17].…”
Section: Introductionmentioning
confidence: 99%